PERSEPSI PENONTON ANAK-ANAK TERHADAP VISUALISASI ANIMASI ACARA SI OTAN DALAM MUATAN KONSEP EDUTAIMENT - Sariati Koyimah; Romdhi Fatkhur Rozi; Dwi Haryanto; Romdhi Fatkhur Rozi (Program Studi Film dan Televisi Universitas Jember, 2022)
Generally, television programs are divided into two parts, which are popular entertaining program called entertainment program and information called news program Television station provides as how that covers the two elements which is known as edutainment. Si Otan program is an edutainment program that explains about animal world. Based on that, to know how far Si Otan program gives influence so that it can broaden knowledge and change perception about animal world. The data of the research were reviewed by using learning theory by Jerome Bruner, the theory that emphasizes the way how people choose, maintain, and actively transform the information. Knowing that Si Otan program can be well accepted by children, so they can understand and draw the information they get from the program. Qualitative research method wasused to know directly the children's perceptions based on their learning process. The result of the research showed that edutainment program that involved animation attracted children's learning interestso that the obtained information became a useful knowledge.